A molecular and ecological analysis of the trematode Plagiorchis elegans in the wood mouse Apodemus sylvaticus from a periaquatic ecosystem in the UK. Issue 3 (19th April 2013) - Boyce, K.; Hide, G.; Craig, P.S.; Reynolds, C.; Hussain, M.; Bodell, A.J.; Bradshaw, H.; Pickles, A.; Rogan, M.T.
Abstract: The prevalence of the digenean Plagiorchis sp. was investigated in a natural wood mouse population ( Apodemus sylvaticus ) in a periaquatic environment. Classical identification was complemented with the use of molecular differentiation to determine prevalence and verify species identity. Use of the complete ITS1-5.8S rDNA-ITS2 and partial 28S rDNA gene sequences have confirmed that the species reported at this location was Plagiorchis elegans and not Plagiorchis muris as reported previously. This underlines the difficulties in identification of these morphologically similar parasites. Plagiorchis elegans is typically a gastrointestinal parasite of avian species but has also been reported from small mammal populations. Although the occurrence of this digenean in A. sylvaticus in the UK is rare, in the area immediately surrounding Malham Tarn, Yorkshire, it had a high prevalence (23%) and a mean worm burden of 26.6 ± 61.5. The distribution of P. elegans followed a typically overdispersed pattern and both mouse age-group and sex were determined to be two main factors associated with prevalence. Male mice harboured the majority of worms, carrying 688 of 717 recovered during the study, and had a higher prevalence of 32.4% in comparison to only 8.7% in the small intestine of female mice. A higher prevalence of 43% was also observed in adult mice compared to 14% for young adults. No infection was observed in juvenile mice. These significant differences are likely to be due to differences in the foraging behaviour between the sexes and age cohorts of wood mice.